Systemic and Systematic Steps of Leadership on Transforming Symbolic into Substantive Characteristic of Madrasah - Mohamad Iwan Fitriani (Jurnal Pendidikan Islam, 2017)
This research studies headmaster’s systemic and systematic steps on transforming symbolic into substantive characteristics of madrasah. The research was conducted at MA Nahdlatu Al-Wathan Putri Narmada, a female Islamic senior high school, in West Lombok, West Nusa Tenggara (NTB). This study used qualitative approach with a case study design. The results found that the observed symbolic characteristics are physical characteristics which distinguish madrasah from other educational institutions. The substantive characteristic is the characteristic of madrasah rooted in its origin, as a historical-genealogical continuance of pesantren. It also preserves the essential, perennial and contextually philosophical values of Islamic teachings, maintains the characteristics of Islam and follows the government policy at the same time because madrasah is a juridical sub-system of the national education with an Islamic integration. Additionally, the head of a madrasah is a translator of Islamic values in his leadership. These Islamic values should be the basis of systematic and systematic leadership.